Hermes - an approach to mass transit guidance with mobile devices - Hagenhoff, Svenja; et al. (2007)
Mobility, understood as the possibility to move around, is an important part of human life. Sociologists have even called mobility a vital principle for the individual and society. Mobility needs may be satisfied in several ways: independently by motorized and non-motorized individual traffic, by means of mass transit or by mixed forms like taxis or park and ride systems. In regard of the negative effects of motorized individual traffic on the environment and the traffic situation in cities it is generally agreed that mass transit ought to be strengthened. A main problem of mass transit systems is the complexity of their usage. Time tables have to be found and understood, connections must be combined and tickets purchased. This problem could be improved by using mobile end devices. This article presents Hermes, a software to be installed on smartphones and PDAs that supports the user in all steps of mass transit usage - from studying the time table to purchasing a ticket and footpath-navigation. Hermes accompanies the user in a process-oriented way and automatically adapts to changing environmental situations.
Keywords: Mobile Anwendungen; Technologien